Course implementation of Mahara e-portfolio: university students’ perspective - Součková Zuzana (Journal of Language and Cultural Education)
The paper investigates the feedback from 2nd and 3rd year students in a teacher training programme as part of the e-portfolio course implementation. Mahara e-portfolio platform was used in a compulsory elective course to enhance the learning experience and provide online space for completing various reading, listening, writing, speaking skills, and vocabulary tasks. The research adopts a qualitative approach and analyses expectations, fears, and contributions (before the implementation) related to e-portfolios and likes, dislikes, and suggestions (after the course completion). The paper reflects the students’ first-hand experience with e-portfolios and seeks to contribute to the growing area of research on this topic. Based on the data, the expectations towards e-portfolios were relatively positive. The students showed concerns, especially over technical issues and digital skills. As to the potential contribution, the students highlighted the interactive nature of e-portfolios. At the end of the course, the students appreciated especially peer-to-peer learning.